7LI/6LI AND 11B/10B VARIATIONS IN CHONDRULES FROM THE SEMARKONA UNEQUILIBRATED CHONDRITE - Chaussidon M.; Robert F. (My University, 1998)
Three excentroradial pyroxene chondrules from the Semarkona unequilibrated chondrite were analysed by ion microprobe mass spectrometry for their Li-Be-B concentrations and Li and B isotopic compositions. The concentrations range for Li between Li/Si = 7.6x10-6 and 5.3x10-5, for Be between Be/Si = 8.3x10-8 and 4.1x10-6 and for B between B/Si ~ 2.5x10-7 and 1.3x10-4. δ7Li values range from -12.7%% to +34.8%% (i.e. 11.86 < 7Li/6Li < 12.44), 85% of the values being however at +10+/-10%%, with an average for the three chondrules of +10.7+/-5.8%% for Sem1-C, +15.1+/-9.7%% for Sem1-G and +7.8+/-9.0%% for Sem1-M. δ11B values range from ~-42%% to ~+44%% (i.e. 3.86 < 11B/10B < 4.23), 87% of the values being however between ~-40%% and +10%%, with average δ11B values of -7.0+/-24.7%% for Sem1-C, -12.2+/-14.9%% for Sem1-G and -10.9+/-8.9%% for Sem 1-M. These variations are not ascribed to isotopic fractionation processes linked to chondrule formation but are interpreted as relicts of isotopic heterogeneities in the chondrule precursors. From the statistical distribution of δ11B and δ7Li the maximum sizes of the present day isotopic heterogeneities in chondrules can be amounted at ~10 μm, but the presence of Li and B isotopic anomalies at the micron level cannot be ruled out. The δ11B-δ7Li ranges suggest that solar system Li-Be-B results from the mixing of several nucleosynthetic sources: (i) the diffuse interstellar medium where B is produced by high energy spallation reactions in galactic cosmic rays (GCR), (ii) dense molecular clouds where B is produced by low energy spallation reactions and (iii) big-bang nucleosynthesis to account for the 7Li excess compared with the theoretical prediction of (i) and (ii). An efficient isotopic homogenization of these three components took place either during planetary processes or in the interstellar medium at a galactic scale. The comparison with the present day 7Li/6Li and 11B/10B in the interstellar medium shows that these ratios were probably constant in the galaxy since 4.5 Gyr ago.
Keywords: LITHIUM; BORON; ISOTOPES; CHONDRULES; SEMARKONA METEORITE; COSMOCHEMISTRY